The impact of COVID-19 (Coronavirus) on children and young people with Down syndrome in the United Kingdom - Pagnamenta, Emma; Hodgkinson, Penny; Davidson, Rosemary; Joffe, Victoria L. (Frontiers in Psychology, 2023)
The COVID-19 pandemic had a profound impact across the globe. Evidence suggests children with Special Educational Needs and Disabilities and their families experienced impacts on well-being and disruptions in support from education and health services. This study investigated the impact of measures associated with the COVID-19 pandemic on children and young people (CYP) with Down syndrome in the UK, specifically changes in speech, language and communication abilities, behaviour, social, emotional and mental health and access to education and healthcare services. 46 parents/carers of CYP with Down Syndrome (aged 2-25 years) completed an online survey between June and September 2020. Parents/carers frequently reported deterioration in speech, language and communication, literacy and attention skills since the onset of the pandemic. Deterioration in social and emotional wellbeing and behaviour, including greater reliance on adults were also reported for some CYP with Down syndrome. Parents reported challenges with home-schooling and reductions in support from education and community services. Preferences for support during COVID-19 were for professional support or from other parents. These findings have implications for the support that is now needed for CYP with Down syndrome and their families and for periods of social restrictions in the future.